Secure medical record sharing using blockchain and elliptic curve cryptography - Kais, Emrul; Rabbi, Fazle; Adon, Sad Murshid Khan; Chowdhury, Mohibul Hassan (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.